Pengaruh Penerapan Perspektif Balanced Scorecard Terhadap Kinerja Usaha Mikro Kecil Menengah (UMKM) Kabupaten Jepara - Ilham Wahyudiarso; Ronny Malavia Mardani; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The balanced scorecard is a performance measurement and management system that views the company from four perspectives, namely financial, customer, internal business processes and learning and growth perspectives to improve strategic decisions in achieving company goals and provide managers or SMEs with an understanding of business performance. The advantage of implementing the Balanced Scorecard is to be able to provide a measure that can be used as a basis for strategic improvement. This study aims to examine and analyze the influence of financial perspectives, customer perspectives, internal business process perspectives and learning and growth perspectives on SMEs performance. The object of this research is SMEs in Jepara Regency. Jepara Regency in 2022, namely 740 SMEs. The sampling technique, namely incidental sampling, obtained a total sample of 88. The data analysis method was through multiple linear regression analysis. The results of the study show that the financial perspective, customer perspective, internal business process perspective and learning and growth perspective simultaneously have a significant effect on the performance of SMEs. Partially, the financial perspective and internal business process perspective have a significant effect on SMEs performance, while the customer perspective and learning and growth perspective have no significant effect on SMEs performance. Keyword: Financial Perspectives, Customer Perspectives, Internal Business Process Perspectives, Learning and Growth Perspectives, SME Performance